Intelligent cooling system used in manufacturing of thin-film solar cell - LI JIAXIAN; ZHANG YIXI (2010)
The invention discloses an intelligent cooling system used in manufacturing of a thin-film solar cell. The system comprises a heating cavity, at least one temperature sensor, a heating element, a fan unit and a control unit, wherein the heating cavity is used for accommodating a cooling gas to be heated; the at least one temperature sensor is used for detecting the temperature of a thin-film solar cell substrate in a process cavity and the temperature of the cooling gas in the heating cavity; the heating element is arranged in the heating cavity and used for heating the cooling gas in the heating cavity; the fan unit is arranged in the heating cavity and used for cooling the cooling gas in the heating cavity; and the control unit can automatically control the output of the heating element and the fan unit according to the detected substrate temperature to raise and reduce the temperature of the cooling gas so that the difference between the temperature of the introduced cooling gas and the detected substrate